Training on Utilization of Based Learning Media Virtual Reality for City Science Teachers Jeneponto - Baharuddin, Hendra; Riskawati, Riskawati (Pustaka Digital Indonesia, 2022)
Activity devotion to community (PkM) aim to: (1) provide introduction to science teachers at Jeneponto Junior High School regarding Virtual Reality learning media as an alternative learning media IT based, and (2) to train science teachers at Jeneponto Junior High School For capable use learning media based on Virtual Reality. Activity done with method training carried out during 3 stages, stage First training related introduction to various learning media used in accordance with development Revolution Industry 4.0 is one of the media used as a learning medium based on Virtual Reality. Training stage two with material about training use of learning media Deep Virtual Reality based learning as well as stage third do evaluation and strengthening. Activity training carried out responses positive of the teachers indicated with enthusiasm during activity as well as attitude positive for applied learning media Deep Virtual Reality based activity learning in accordance with development technology Information in the Age of Revolution Industry 4.0. The training participants were very interesting and enthusiastic in participating in the training activities. Participants also gain knowledge, skills and motivation by using Virtual Reality-based learning media. Participants responded positively to training activities and were able to apply various learning media in the learning process so as to improve the quality of learning.